Ortner’s Syndrome: A cause of unilateral vocal cord paralysis - Palanisamy, Vanitha; Doshi, Kevin Suresh; Tengku Nun Ahmad, Tengku Ezulia; Abu Bakar , Mohd Zulkiflee; Rajagopalan, Raman (Global Journal of Medical and Clinical Case Reports, 2017)
Ortner’s syndrome is rare syndrome characterised by hoarseness of voice due to recurrent laryngeal nerve involvement in cardiovascular disease. This report presents a case of left laryngeal paralysis caused by an aortic arch aneurysm and to highlight the importance of an otorhinolaryngology evaluation along with a thoracic radiologic study.